On a newly discovered monument of the Old Russian literature - G. A. Lonchakova (Библиосфера, 2016)
The article represents a newly discovered essay «An eulogy to Saint Sabbatius Solovetsky»; considers its textual relations to the Life of Zosima and Sabbatius Solovetsky in the I stylistic version and the eulogy to Saint Varlaam Khutynsky by Pachomius Logofet; supposes the time of this literary monument creation